Zeugnisse des Okkulten: Literatur und Esoterik im Wiener Fin de Siècle - Kaufmann, Kira (Brill, 2025)
This study examines the interactions between literature and occultism in Vienna around 1900. For the first time, it examines a comprehensive and disparate corpus of texts and asks how philological work relates to a worldview in which nothing is accidental and everything is meaningful. Occult knowledge operates in the realm of "border science": It intrudes into authorized areas and pushes the conventional boundaries of science, society, politics, and art. In short, it affects the self-image of a modern, progressive life around 1900. Literature is just one artistic form of expression among many in which boundaries are explored and pushed. At the heart of this study are nine thematic complexes that make the occult tangible in its everyday manifestations through a variety of literary and non-literary texts.